Increased Detectability of Alpha Brain Glutamate/Glutamine in Neonatal Hypoxic-Ischemic Encephalopathy - Pu, Yonglin; Li, Qing-Feng; Zeng, Chao-Mei; Gao, Jian; Qi, Jing; Luo, De-Xin; Mahankali, Srikanth; Fox, Peter T.; Gao, Jia-Hong (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Proton MR spectroscopy (MRS) detectability of brain glutamate/glutamine (Glx) is increased in hypoxic-ischemic insults and is implicated in the neuronal injury and death that follows. Our aim was to correlate the proton MRS detectability of α-CH protons of Glx (α-Glx) with the Sarnat stage of neonatal hypoxic-ischemic encephalopathy (HIE).METHODS: Initial and follow-up proton MRS studies at 1.9 T were performed in 28 neonates aged 1 to 7 days (seven healthy control subjects and 21 with HIE: 10 mild, nine moderate, and two severe) and in 12 neonates aged 13 to 17 days (12 with HIE: eight mild, three moderate, and one severe), respectively. Both point-resolved spectroscopy (PRESS) and stimulated-echo acquisition mode (STEAM) sequences were used. The spectral volume of interest was in the basal ganglia, thalami, and adjoining regions. The detectability of α-Glx was assessed by two different parameters: the detection rate of the α-Glx peak and the peak-area ratio of α-Glx to creatine and phosphocreatine.RESULTS: On both the initial and follow-up PRESS studies, all the neonates with moderate and severe HIE showed an α-Glx peak, compared with one healthy control subject in the initial study and one neonate with mild HIE in both the studies. They also demonstrated a significantly higher peak-area ratio of α-Glx/(creatine and phosphocreatine) on both the initial and follow-up studies. The peak-area ratios in neonates with HIE positively correlated with the Sarnat stage of HIE on both the initial and follow-up studies. Neonates with moderate and severe HIE also showed a consistently higher α-Glx peak on both the initial and follow-up studies with the STEAM sequence.CONCLUSION: Proton MRS detectability of α-Glx is increased in moderate and severe HIE and correlates with the Sarnat stage of HIE.